Penggunaan Balok Dalam Meningkatkan Kreativitas Anak Usia 5-6 Tahun di PAUD Sps Tp Melati Cisolok Kecamatan Cisolok Kabupaten Sukabumi - Winarni, Wiwin; Elnawati, Elnawati; Awal Maulana, Redi (PT. Alahyan Publisher Sukabumi, 2025)
One of the educational game tools is blocks, which are usually made of wood. Three-dimensional blocks have various shapes, such as cubes, cylinders, tubes, cones, spheres, spheres, triangular prisms, rectangular pyramids, or pyramids, and various colors that are attractive to children. Block media helps children imagine and think about turning it into a certain shape. They are also trained to put blocks together one by one, and they can think about what to make. If children receive continuous practice, their imagination and creative abilities will develop. The more unique ideas children have, the more creative they are. The aim of this research is to find out how games influence children's creativity in children aged 5-6 years in group B PAUD SPS TP Melati Cisolok. This research uses classroom action research methods.